Uji Aktivitas Antibakteri Ekstrak Daun Kelor (Moringa oleifera) Terhadap Staphylococcus aureus - Andini, KD Ayu Asti; Dharmawan, Ade; Layanto, Nicolas (Jurnal MedScientiae, 2024)
Plants are a source of various types of chemical compounds that have many benefits, one of which is as antibacterial agents. One of the plants known for its antibacterial properties is the moringa leaf (Moringa oleifera). This research aims to determine whether moringa leaves (Moringa oleifera) possess antibacterial activity, as well as to identify the minimum inhibitory concentration and minimum bactericidal concentration of moringa leaf extract against Staphylococcus aureus bacteria. This research method uses the dilution method. The results of the research indicate that moringa leaf extract has antibacterial activity against Staphylococcus aureus at concentrations of 20%, 40%, and 80%. It was found that as the concentration increases, the antibacterial activity inhibiting the growth of Staphylococcus aureus also increases.